Efektivitas Mata Kuliah Bahasa Indonesia Dalam Rangka Meningkatkan Kemampuan Menulis Tugas Akhir Mahasiswa - Mahsunah Etik R (Jurnal Maritim Polimarin, 2019)
The research entitled Efektivitas Mata Kuliah Bahasa Indonesia Dalam Rangka Meningkatkan Kemampuan Menulis Tugas Akhir Mahasiswa (Effectiveness of Bahasa Indonesia Courses in Order to Improve the Writing Ability of Student's Final Project) is a qualitative study with the object of research of students with a total of 50 people. This study aims to understand the role of the Indonesian language in improving the ability to write final assignments. For data collection techniques in this study using observation, documentation and questionnaire techniques. The types of data sources are primary and secondary. Then for data processing techniques by collecting data, editing data and interpreting data. The conclusion of this study is based on the standard size that is in accordance with the reference. Research and Development of DEPDAGRI now KEMENDAGRI (Ministry of Internal Affairs) applied with the results obtained from existing research data, the number of positive values that show the number 80.31%, which means the expected level of achievement is very effective because it gets 80%. Based on questionnaire data obtained by students learning about difficulties and they need help to be able to learn Indonesian Language courses for the sake of carrying out the final assignment they have to do after internship. 35.3% of them requested that the lecturers explain. 8.9% of them requested assignments and training and requested additional assistance. In addition, they requested that the lecturers explain briefly, because finally 5% answered the lecturers explained too quickly. As many as 4% of students answer Indonesian difficult because there is too much material and as many as 1% answer between lecturers and each other explain it differently.